Women, race, work, and Rural Education during the Covid-19 pandemic - Andrea Francine Batista; Carolina Orquiza Cherfem; Maria Eloa Gehlen (Universidade Federal do Norte do Tocantins, 2024)
This article is the result of an interinstitutional research entitled "Education and Rural Schools in times of the COVID-19 pandemic" that began during 2020. We performed the research through a quantitative approach, with the application of questionnaires with students and former students from the courses of Rural Education, Pedagogy of Land and Indigenous Pedagogy. After this first moment, we developed online qualitative interviews. We seek to present an analytical outline based on the data collected, especially at the intersections between class, women, race, work and rural education. Although it was not the centrality of the investigation, it pointed out a series of data that came from the concrete lives of these women and required a more systematic analysis. To present this debate, the article emphasized three major themes, namely: Women, Class, Race and Ethnicity through the profile of the women who participated in the research; Work, Gender and Race in Rural Education during the pandemic; and the impacts of the pandemic on women in Rural Education. Among the main results, there is a greater presence of women and black people engaged in Rural Education, most of whom are mothers. Among the main impacts that these women suffered in their lives, the increase in work, decreased income and dedication to their studies and their children during the pandemic stand out, which was precarious for most of them.